Hey there!
Answer = -14
Explanation:
Let's solve your equation step-by-step.
x + 2 = -12
Subtract 2 from both sides:
x + 2 - 2 = -12 - 2
x = -14
So therefore, that is how you found your answer: x = -14
In order to convert centimeters to inches, you use the following equation:
1 inches = 2.54 cm
If you have to convert, for example, 4 inches, you proceed as follow:
4 inches* (2.54cm/1 inches) = 10.16 cm
That is, you multiply the quantity that you want to convert, by the quotient between 2.54cm and 1 inches.
Step-by-step explanation:
LHS=(1-sin60)/cos60
=(1-√3÷2)/1÷2
=2(1-√3÷2)
=2-√3
RHS=(1-tan30)/(1+tan30)
={1-(1÷√3)}/{1+(1÷√3)}
={(√3-1)/√3}/{(√3+1)/√3}
=(√3-1)/(√3+1)
={(√3-1)(√3-1)}/{(√3+1)(√3-1)}
=(3-√3-√3+1)/(3-1)
=(4-2√3)/2
=2-√3
Therefore LHS=RHS
Answer:
25%
Step-by-step explanation:
12=100%
3=25%
9=75%